Drug-Releasing Antibacterial Coating Made from Nano-Hydroxyapatite Using the Sonocoating Method - Khaled AbouAitah; Monika Bil; Elzbieta Pietrzykowska; Urszula Szałaj; Damian Fudala; Bartosz Woźniak; Justyna Nasiłowska; Anna Swiderska-Sroda; Maciej Lojkowski; Barbara Sokołowska; Wojciech Swieszkowski; Witold Lojkowski (Nanomaterials, 2021)
Medical implant use is associated with a risk of infection caused by bacteria on their surface. Implants with a surface that has both bone growth-promoting properties and antibacterial properties are of interest in orthopedics. In the current study, we fabricated a bioactive coating of hydroxyapatite nanoparticles on polyether ether ketone (PEEK) using the sonocoating method. The sonocoating method creates a layer by immersing the object in a suspension of nanoparticles in water and applying a high-power ultrasound. We show that the simple layer fabrication method results in a well-adhering layer with a thickness of 219 nm to 764 nm. Dropping cefuroxime sodium salt (Cef) antibiotic on the coated substrate creates a layer with a drug release effect and antibacterial activity against Staphylococcus aureus. We achieved a concentration of up to 1 mg of drug per cm2 of the coated substrate. In drug release tests, an initial burst was observed within 24 h, accompanied by a linear stable release effect. The drug-loaded implants exhibited sufficient activity against S. aureus for 24 and 168 h. Thus, the simple method we present here produces a biocompatible coating that can be soaked with antibiotics for antibacterial properties and can be used for a range of medical implants.